Selective head-and-neck cooling acutely following sports-related concussion reduces time from play in Swedish elite ice hockey players - Marklund, N.; Al-Husseini, A.; Gard, A.; Andersson, E.; Tegner, Y. (BMJ Open Sport & Exercise Medicine, 2022)
Introduction Sports-related concussions (SRCs) are an increasingly recognized health problems and treatment options are scarce. We tested the hypothesis that immediate selective head-neck cooling shortens return-to-play (RTP) in concussed ice hockey players.